Analysing Indonesian words "mencari ilmu," "menuntut ilmu," "menimba ilmu," and "menggali ilmu": An active learning in Indonesia - Wajdi, Majid; Suarja, I Ketut; Susanto, Budi; Mustafa, Muhammad; Udoudom, Uduak Imoh; Claridad, Norberto Fabi (Journal of Language and Pragmatics Studies, 2024)
This study goes into the rich idioms of the Indonesian language related to learning, specifically focusing on "mencari ilmu" (searching for knowledge), "menuntut ilmu" (demanding knowledge), "menimba ilmu" (drawing water of knowledge), and "menggali ilmu" (unearthing knowledge). These terms provide nuanced perspectives on the nature of active learning in Indonesian culture. The study aims to (1) Analyse the literal and figurative meanings of each term within the context of active learning. (2) Explore how these terms reflect different stages and approaches to the learning process. (3) Highlight the values and principles embedded within each term that contribute to effective learning. The study employs a document analysis approach, meticulously examining existing literature and scholarly works on Indonesian language, education, and cultural values. Additionally, the author, as a native Indonesian speaker, utilizes introspection to provide in-depth insights and personal interpretations of the terms. The analysis reveals subtle differences in meaning and emphasis between the terms, showcasing the multifaceted nature of active learning. Each term illuminates a specific aspect of the learner's role, from the initial spark of curiosity to the dedicated pursuit of knowledge, the patient extraction of established information, and the adventurous exploration of uncharted territories. The study concludes that these Indonesian idioms offer valuable lessons for active learning beyond cultural boundaries. They emphasize the importance of curiosity, determination, effort, and independent exploration in the pursuit of knowledge. Cultivating an active learning mindset empowered by these principles can pave the way for individuals to become lifelong learners and contribute meaningfully to society.